Catalytic wet air oxidation of olive mill wastewater - Gomes, Helder (2006)
The objective of this work was to study the suitability of catalytic wet air oxidation (CWAO) for the treatment of olive mill wastewater (OMW). Accordingly, experiments were performed in a high pressure reactor at 100ºC and 200ºC under an oxygen partial pressure of 6.9 bar, using carbon supported platinum (1wt.% Pt) and iridium (5 wt.% Ir) catalysts prepared by incipient wetness impregnation. Both catalytic systems showed a very high activity in the total organic carbon (TOC) removal of the effluent, an increase in TOC removal relatively to non-CWAO being observed. At 200ºC, complete TOC and colour removal was obtained with the Pt/C catalyst after 8 h of reaction. At 100ºC, the results indicate that a certain fraction of compounds in the effluent (low molecular weight recalcitrant carboxylic acids)could not be removed even after prolonged reaction time. A kinetic model was developed taking into account catalytic and noncatalytic reaction, formation of refractory compounds and catalyst deactivation. A very good agreement between the model results and the CWAO experimental data at 200ºC was found. The results obtained in this work indicate that Pt/C is a promising catalyst for the CWAO of OMW.